Creating climate-informed physician leaders: The evolution of a physician fellowship in climate and health science policy - Wheat, Stefan; Chekuri, Bhargavi; Sorensen, Cecilia; Rochford, Rosemary; Lemery, Jay (Frontiers in Medicine, 2022)
Climate change poses numerous near and long-term challenges for our society, and the human health consequences are increasingly recognized as unprecedented. Responding to these health hazards requires a healthcare workforce composed of climate-informed clinicians. As trusted messengers, physicians play a vital role in informing and preparing the public for health impacts of climate change. We describe an evolving graduate medical education fellowship for physicians from all specialties capable of training leaders in this field. Our program pairs fellows with federal and non-governmental partners to provide expertise in climate policy and empower them to be change agents. The accelerating response to climate change from the federal government coupled with an increased recognition of the impacts of climate hazards on health demands a climate-informed clinical workforce. The expansion of this fellowship to accommodate trainees from multiple specialties and its innovative structure leveraging local and national partnerships sets a standard for how similar programs can be developed in addressing the greatest public health threat and opportunity of the century.